Light At the End of The Tunnel: Re-Storying the Experiences of Teacher- Covid19 Survivors (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2021)
The continued service at the frontline of educational delivery in the time of COVID19 pandemic situates teachers to susceptibility that is no less critical. This study aimed to tell the experiences of teachers who were in the throes of COVID-19 disease and have recovered, through the narration of their personal stories. Narrative Inquiry was employed and facilitated by the use research interviews and written accounts of 4 teacher-survivors. Using Narrative Thematic approach in data analysis, themes were developed and were formatted in a literary chronological sense of the pre, during and post COVID19 stages of their journey to tell a cohesive narrative story. The plot started with Skepticisms and disbelief that describe the pre-COVID stage. Guilt, Anxiety and Shame; Fraud Information and Disclosure; Stigmas and Discrimination; and experiences pertaining to Temporality and Place; to their Being a Teacher; and to Relationship and Sociality, capture their During-COVID19 stage. The common accounts of Lessons and New Beginnings articulate the Post-COVID19 Stage. Recommendations to help advance the public’s understanding of the experiences of these teacher-survivors were also explicated.